Relaksacja belek z płyt wiórowych - analiza wyników badań rozpoznawczych = Relaxation in chipboard beam - analysis of exploratory experimental tests - Socha, Tomasz; Kula, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper concerns problems of rheology in wood-based beams made of chipboard "PowerBoard" produced by SWISS KRONO. Theoretical models of the behaviour of chipboard and results of exploratory experimental relaxation tests are presented. Material of this beam is described with equations for linear viscoelastic media (three-, four- and five-parameter rheological models).
Keywords: liniowa lepkosprężystość; materiały drewnopochodne; reologia; linear viscoelasticity; wood-based materials; rheology